Enhancing routing energy efficiency of Wireless Sensor Networks - Zaman, N. (Institute of Electrical and Electronics Engineers Inc., 2015)
Nowadays Wireless Sensor Networks WSNs are playing a vital role in several application areas ranging health to battle field. Wireless sensor networks are easy to deploy due to its unique characteristics of size and self-organizing networks. Wireless sensor nodes contain small unchangeable and not chargeable batteries. It is a resource constraint type network. Routing in WSN is most expensive task as it utilizes more power resources. This paper is intended to introduce energy efficient routing protocol, known as Position Responsive Routing Protocol (PRRP) to enhance energy efficiency of WSN. Position responsive routing protocol differs in several ways than other existing routing techniques. Position response routing protocol approach allows fair distribution of gatewayļuster head selection, maximum possible distance minimization among nodes and gatewaysļuster heads to utilize less energy. Position responsive routing protocol shows significant improvement of 45 in energy efficiency of wireless sensor network life time as a whole by increasing battery life of individual nodes. Furthermore PRRP shows drastic increases for data throughput and provide better solution to routing energy hole due to it fair distributed approach of gateway selection. This work is the extension of Energy efficient routing protocol for wireless sensor network published in IEEE ICACT 2014. Â© 2015 Global IT Research Institute (GiRI).